HUBUNGAN ANTARA DERAJAT PENYAKIT DENGAN JUMLAH LIMFOSIT ABSOLUT PADA PENDERITA OSTEOARTRITIS LUTUT DI RUMAH SAKIT UMUM AL-FAUZAN PERIODE TAHUN 2019-2021 - Fahira Shafira Qori Mufida (2022)
Knee osteoarthritis (OA) is a degenerative joint disease due to chronic and prolonged inflammation of the cartilage of the knee joint. Chronic and prolonged inflammation in patients with knee OA will cause defects in the cartilage of the knee joint. The wider the defect, the more extensive the process of cartilage degeneration of the knee joint and knee OA will be more severe. Considering that radiological and arthroscopic diagnostic test are expensive, so it is necessary to use other alternatives as a marker of knee OA grading scale such as absolute lymphocyte count (ALC). ALC is a marker of inflammation that has not been used in patients with knee OA. The purpose of this study was to determine the correlation between knee OA grading scale with ALC in knee OA patients. This study used cross sectional design and a total of 75 patients from the orthopedic clinic of Al-Fauzan General Hospital period of 2019-2021. Statistical analysis with Chi-Square test in the form of 2x2 and Fisher's alternative test. The results showed that the majority of ALC ≥ 1,5 x 109/L who had mild knee OA grading scale were 46 people (69,7%) and the majority of ALC < 1,5 x 109/L severity knee OA grading scale were 5 people (55,6%). Statistical tests showed no significant correlation between knee OA grading scale with ALC in knee OA patients (p = 0.455; p > 0.05). The conclusion, there was no significant correlation between knee OA grading scale with ALC in knee OA patients at Al-Fauzan General Hospital period of 2019-2021. Chronic and prolonged inflammation in knee OA causes lymphocyte proliferation so that ALC increases.